Meg : hell's aquarium - Alten, Steve (Variance, 2009)
David Taylor, the twenty-one-year-old son of Jonas Taylor, agrees to escort two of Angel's litter to Dubai, where a royal prince is building the largest aquarium in the world, unaware that he is being set up to lead an expedition into the dangerous Panthalassa ocean hidden beneath the Philippine Sea Plate.